hubungan antara otot lengan, otot tungkai, dan otot perut terhadap smash bola voli pada club bina voli sepanjang masa - Anggi Anggraeni; Wahyu Setia Kuscahyaning Putri; Olivia Dwi Cahyani (Universitas Hamzanwadi, 2026)
This study was motivated by the phenomenon observed in the field, where approximately 35% of athletes still experience difficulties in executing smashes, presumably due to suboptimal specific physical training programs. The study aims to analyze the relationship between arm, leg, and abdominal muscle strength and volleyball smash ability, as well as to identify the relative contribution of each variable. The method use is quantitative correlational with a population of 30 athletes from the Bina Voli Sepanjang Masa Club (total sampling). Data were collected through physical tests (push-ups, vertical jumps, sit-ups) and smash skill tests, analyzed for using multiple linear regression. The results showed a very strong relationship with a coefficient of determination (R²) of 0.965, meaning that 96.5% of the variation in smash ability could be explained by these three variables. Partially, leg muscle strength contributed the most (31.0%), followed by arm muscles (26.3%), and abdominal muscles (5.5%). The study concluded that smash ability is greatly influenced by the athlete's physical condition, with the recommendation that training programs prioritize strengthening leg explosive power, supported by increased arm strength and abdominal muscle stability.